Ecological Influences on Employees' Workplace Sedentary Behavior: A Cross-Sectional Study. Issue 8 (November 2018) - Wilkerson, Amanda H.; Usdan, Stuart L.; Knowlden, Adam P.; Leeper, James L.; Birch, David A.; Hibberd, Elizabeth E.
Purpose: The purpose of this study was to explore the relationship between ecological factors and occupational sedentary behavior (SB). Design: Cross-sectional online survey. Setting: Participants were employees recruited from a large, public university in the Southeastern United States from August to November 2016. Participants: The final sample included 527 (56% response rate) employees. Measures: Data were collected through an 87-item survey using previously validated scales that assessed occupational SB, perceived behavioral control, barrier self-efficacy, self-regulation strategies, organizational social norms, office environment, and worksite climate. Analysis: One-way analysis of variance analyses were used to determine differences in occupational SB by demographic factors. A multivariate regression model was used to determine significant ecological determinants of occupational SB. Results: Mean SB was 342.45 (standard deviation = 133.25) minutes. Significant differences in SB were found by gender, education, and employment classification. Barrier self-efficacy and workplace connectivity, which evaluates the spatial layout of the office setting that may impact mobility within the workplace, were significant predictors of SB in the multivariate model. Conclusion: Results from this study provide new information regarding the potential impact of workplace barriers and connectivity on occupational SB. The findings from this study support the inclusion of intervention modalities to minimize workplace barriers and increase workplace connectivity to increase workplace mobility and decrease SB.